Athletic intruders : ethnographic research on women, culture, and exercise - Bolin, Anne; Granskog, Jane (SUNY series on sport, culture, and social relations., 2003)
Informed by feminism and the fields of anthropology and sociology of sport, this anthology investigates women's place in sport and exercise from a sociocultural perspective, documenting women's struggle into the sports arenas of male hegemony. The nine ethnographic case studies explore issues of identity, embodiment, and meaning in various sports and exercise, including triathlons, aerobics, basketball, bodybuilding, weightlifting, motorcycle riding, softball, casual exercise, and rugby. [from publisher's advertisement].